Pengaruh Budaya Sekolah Islami terhadap Perilaku dan Karakter Siswa - Indri A. Hapid; Maya Sari; Arnila Sidae; Rahma Sabbu; Nailah Alfarafisha Laiya (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Character education based on religion is highly needed to cultivate a generation that is both intelligent and noble in character. An Islamic school culture serves as a means of instilling values through habits, rules, and traditions. The thoughts of Al-Ghazali, Ibn Khaldun, Ki Hajar Dewantara, and Thomas Lickona emphasize the need to combine knowledge, deeds, exemplary behavior, and collaboration among schools, families, and communities. Previous research indicates that routine religious activities strengthen religious awareness, discipline, honesty, responsibility, and tolerance. The challenges include differences in value application at home, diverse student backgrounds, time constraints, and the negative impacts of the external environment and digital media. The novelty of this study lies in the comprehensive mapping of the relationship between Islamic culture, character, and its supporting and inhibiting factors within a single framework. The method used is library research, which is described descriptively.